PENGEMBANGAN MODEL PEMBELAJARAN SAINS MELALUI BERMAIN DI TAMAN KANAK-KANAK - PALENEWEN, EVIE (JURNAL PENDIDIKAN ANAK USIA DINI, 2012)
The objective of this research and development is to develop a model of science learning program through play activities of children in kindergarten. The research was conducted in DKI Jakarta, by conducting surveys on five kindergartens as the sample during the pre-develompment phase, and a kindergarten at East Jakarta was purposely chosen for implementation phase of field-testing. Research conclussions: (1) the developed model of learning science through play is effective when implementing in kindergarten, (2) the model is developed based on the crossed study of literature and survey which mainly showed that science learning program at kindergarten were dominantly lean on the theacherâs knowledge in science, that is infact most teacher realized that their science knowledge were minimum. (3) the structure the model of science learning through play developed, includes; description of themes, learning competences and indicators, learning objectives focused on science process skills and attitude, conceptual web of play, description of esentials science material for teacher, the scenario of learning activities and evaluation.Keywords: model of science learning through play, science process, esentials sciences material